A Comprehensive Review: Molecular and Genetic Background of Indirect Inguinal Hernias - SOMUNCU, SALİH; SOMUNCU, SALİH; Somuncu, Ozge Sezin (My University, 2021)
Background: The occurrence of indirect inguinal hernias (IIH) is 5 times more prevalent than that of direct inguinal hernias (IH) and it is 7 times more common in males, owing to the attendance of the processus vaginalis (PV) throughout testicular descent. Summary: In children, the immense mainstream of IH is indirect. The progress of IIH development in children is instigated with a patent PV, which is mostly treated by simple herniorrhaphy. Syndromes of the collagen, microfibril, elastin, and glycosaminoglycan constituents of the extracellular matrix may attend to the development of IH. Our recent research showed that the lack of epithelial-mesenchymal transition (EMT) in children contributes to the development of IIH, while the scenario is defined as the opposite in adults. However, there is still a lack of knowledge on all of the genetic and molecular causes of the disease. Key Messages: Here we aimed to review the published genetic background of IH, the deficiencies of connective tissue causing the disease, recently defined molecular pathways involved including EMT, and possible recurrence reasons. This comprehensive study can deliver an analytic outline aiding to define patients with IH combined with fundamental genetic diseases.
Keywords: Epithelial-mesenchymal transition; Genetics; Indirect inguinal hernia